IMPLEMENTASI SEKOLAH RAMAH ANAK (SRA) PADA SEKOLAH PERCONTOHAN DI SD PEKUNDEN 01 KOTA SEMARANG SEBAGAI UPAYA UNTUK MENDUKUNG PROGRAM KOTA LAYAK ANAK (KLA) - Artadianti, Kiki; Subowo, Ari (Journal of Public Policy and Management Review, 2017)
Children are not an object so that can rudely treated, they have own characteristic that need to be determined by the differentiation towards their treatment, with an aim to protect and guard them for supporting their future. At the District / City level, regulations and policies on child protection tend to focus when a child has entered into legal matters or has committed break the law, the actions of the government are limited to rehabilitation and often ignore the aspects of prevention. This prevention aims to prevent a child from taking unlawful acts. This research is to describe child-friendly school program as an effort to prevent child face with law (ABH) in Semarang City. This research uses qualitative approach with the theoretical concept from Mazmanian & Sabatier. The results of this research shows that the implementation of child-friendly school program as an effort to prevent child face with law (ABH) in Semarang City has not been implemented optimally yet, because the implementation of child-friendly school program still facing many obstacles like physically violence in school by their teacher or students. Lack of control from parents, as well as environmental influences of children who are factors causing child face with law. Suggestion from researcher are increased cooperation between related institutions, and also doing communication intensity towards their parents. Then, the lack of human resources to guide the student physically become an obstacle to the implementation of child-friendly school.